Societal self-empowerment in Germany: a comparison of Fridays for Future and Corona skepticism - Kirsch, Peter; Kube, Hanno; Zohlnhöfer, Reimut (Springer Fachmedien Wiesbaden, 2023)
Introduction -- What is self-empowerment? -- How much self-empowerment is there in Germany? -- What are the reasons for self-empowerment? -- Discussion -- Conclusion and outlook.